Strategi Pemberdayaan Masyarakat Melalui Program Motivator Ketahanan Keluarga (Motekar) Dalam Masa Pandemi Covid-19 Di Kabupaten Karawang - Poetry Ardeavany Rahma; Gili Argenti; Haura Atthahara (Jurnal Ilmiah Wahana Pendidikan, 2023)
Motekar is a program created by the West Java provincial government in 2014 by following Regional Regulation (Perda) No. 9 of 2014 concerning the Implementation of Family Resilience Development to help empower people who experience family vulnerabilities. This study describes the community empowerment strategy through the Family Resilience Motivator (MOTEKAR) program in Karawang Regency during the COVID-19 pandemic in dealing with family vulnerabilities that occurred in Karawang Regency. This research is qualitative research using descriptive methods and the theory used in this research is the theory of community empowerment strategy by Parsons et.al in (Suharto, 2014) which divides 3 levels or levels of strategy, its the micro-level, mezzo level, and macro level. The micro-level strategy empowers clients individually, the mezzo level strategy empowers using a group as an intervention medium, and the macro-level strategy empowers people who are considered can overcome their problems. The purpose of this study was to determine the extent to which level strategies were fulfilled in the process of implementing empowerment through the Motekar program in Karawang Regency during the COVID-19 pandemic. The results of this study indicate that in the implementation of empowerment there are still 2 strategies that have not been fulfilled.